Implementing group counseling action research to improve students learning motivation - Sukarsini, Made; Budiarta, I Komang Ribek Teja; Suranata, Kadek (Konselor, 2018)
This article reports the results of the group counseling action research activities to improve students’ learning motivation in the Junior High School. The research subject consisted of 36 (14 men and 12 women) students of first grade in the SMP N 3 Singaraja. The action reserachcarried out in these two cycles’ involved 8 observers (consisting of 6 counseling teachers and 2 lecturers). Each cycle held two group guidance class. The procedure of group counseling action review activities in each cycle follows the three stages of the learning action study described by Hopkins and friends which include: (1) planning; (2) action and observation, and (3) reflection. Student learning motivation data were analyzed by quantitatively descriptive statsitic and compared at the end of each siclus by prosent. Data from observations of group counseling activities described by narrated. The results of the group guidance study show that there is an increase in the level of student learning motivation of every siclus. The baseline of students motivation is 68 or in the medium category. At the end of the first cycle, the average student learning motivation was 79 or still in the medium category. While at the end of the second cycle the average student motivation is 84 or in the high category. The results of the study on the implementation of group counseling actions by 8 observers showed an increase in the quality of the group counseling process and an increase in the ability of model teachers in managing group counseling activities from the first cycle to the second cycle